SOSIALISASI PENDAFTARAN DAN PEMBUATAN NIB OSS DI DESA KALIDAWIR TULUNGAGUNG - Lona Chinsia Alfattama; Desi Rahmawati (JANITA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
In the world of Micro, Small and Medium Enterprises (MSMEs), the NIB (Business Identification Number) has a very important role, namely it is an official identity that provides legal recognition for MSME businesses which provides access to various conveniences in doing business. This is intended to provide official value for an identity. issued by the Online Single Submission (OSS) Institute. NIB (Business Identification Number) is the identity number of business actors regulated in the standard classification of Indonesian Business Fields (KBLI). The NIB registration method can be done with OSS by preparing the existing requirements. Through NIB registration, business owners can also obtain other registration documents needed for business licensing such as NPWP, letter of approval for plans for the use of labor and for SIUP. By having an NIB, the legality of business actors will be more legally guaranteed when running their business.